2010
DOI: 10.1002/nag.973
|View full text |Cite
|
Sign up to set email alerts
|

Efficient block preconditioners for the coupled equations of pressure and deformation in highly discontinuous media

Abstract: SUMMARYLarge-scale simulations of flow in deformable porous media require efficient iterative methods for solving the involved systems of linear algebraic equations. Construction of efficient iterative methods is particularly challenging in problems with large jumps in material properties, which is often the case in geological applications, such as basin evolution at regional scales. The success of iterative methods for this type of problems depends strongly on finding effective preconditioners. This paper inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…An inexact version of Eq. 20, along with its nonsymmetric cousin P −1 gGS , was shown in [18] to be very robust preconditioners for Biot's equations on a problem with extreme contrasts in the material parameters. Algorithm 1 shows the necessary steps to implement this preconditioner.…”
Section: Block Preconditioning Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…An inexact version of Eq. 20, along with its nonsymmetric cousin P −1 gGS , was shown in [18] to be very robust preconditioners for Biot's equations on a problem with extreme contrasts in the material parameters. Algorithm 1 shows the necessary steps to implement this preconditioner.…”
Section: Block Preconditioning Methodsmentioning
confidence: 99%
“…The present authors likewise found SA to be a nearly optimal preconditioner for the discontinuous Poisson pressure problem (see [16]) and to perform well on the similarly structured Schur complement approximation found in Eq. 21 (see [18]). …”
Section: The Single-block Preconditionersmentioning
confidence: 96%
See 3 more Smart Citations